A Case of an Orbitocranial Injury with an Unusual Foreign Object - Diciano Jr. David G.; Sabundayo-Tiu Suzanne; Yatco-Omaña Elaine (Journal of Ophthalmic Science, 2021)
Introduction Large impaled object in the orbital region causes severe visual impact and requires specialized care within the shortest time possible. Objectives In this case report, we discussed the approach and management of a patient that presented with a penetrating orbitocranial injury, from management at the emergency unit, diagnostic imaging, referral to other subspecialty, surgical and medical intervention, and post-operative care. Discussion A 36-year old male had an impaled toilet brush on the supero-nasal aspect of the right orbit, with visual acuity of 6/60 and lacerated upper eyelid. The globe had minimal movement on all gazes, but pupil was reactive to light with no afferent defect. On plain cranial and orbital CT-scan, the foreign body entered the anterior and medial aspects of the right orbit penetrating the right superior orbital wall, right medial lamina papyracea, and the lateral and inferior border of the right frontal sinus with its distal tip at the intracranial region at the right frontal lobe compressing the medial rectus along its tract. Two hours after injury, patient underwent wound exploration, removal of foreign body, repair of eyelid laceration, right craniotomy, frontal contussectomy, duraplasty, and JP-drain insertion under general anesthesia. Intraoperatively, there was note of transected canaliculus and avulsed conjunctiva. The medial rectus was intact and attached. The frontal lobe was contused with embedded fragments of right posterior orbital bone with 3cm opening on the dura. Post-operatively, Fluconazole was added to the medications after culture results of the toilet brush tip tested positive for fungal elements. Patient was discharged after 21 days with visual acuity of 6/6 on both eyes and improved ocular movement. Conclusion These types of injury warrants thorough and systematic history taking and physical examination, acquiring pertinent imaging modalities to better visualize the extent of injury, and execute surgical and medical intervention that is multidisciplinary.
Keywords: Orbitocranial Injury